2016
DOI: 10.1101/089425
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prestimulus alpha-band power biases visual discrimination confidence, but not accuracy

Abstract: Oscillations in the alpha-band (8-13 Hz) of human electroencephalographic (EEG) recordings are thought to reflect cortical excitability. As such, the magnitude of alpha power prior to the onset of a near threshold visual stimulus has been shown to predict stimulus detectability. Mechanistically, however, non-specific increases in visual-cortical excitability should result in amplified signal as well as amplified noise, leaving actual discriminability unchanged. Using a two-choice orientation discrimination tas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
74
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(88 citation statements)
references
References 46 publications
12
74
2
Order By: Relevance
“…In line with such a neural underpinning, a series of studies suggested that reduced alpha power correlates with enhanced perceptual sensitivity (Ergenoglu, et al, 2004;Hanslmayr, et al, 2007;van Dijk, Schoffelen, Oostenveld, & Jensen, 2008;Mathewson, Gratton, Fabiani, Beck, & Ro, 2009;Busch, Dubois, & VanRullen, 2009;Obleser & Weisz, 2012). Yet, recent studies suggested a different picture whereby the alpha power does not modulate perceptual sensitivity or accuracy per se but rather reflects a bias in perceptual decision making (Limbach & Corballis, 2016;Iemi, Chaumon, Crouzet, & Busch, 2017;Samaha, Iemi, & Postle, 2017;Craddock, Poliakoff, El-deredy, Klepousniotou, & Lloyd, 2017;Iemi & Busch, 2018;Wöstmann, Waschke, & Obleser, 2018). While the precise role of alpha in a mechanistic cascade of sensory-decision processes remains debated, we here consider alpha oscillations from a new perspective, through the prism of idiosyncratic and temporary biases.…”
Section: A Mechanistic Role Of Alpha Powermentioning
confidence: 98%
See 1 more Smart Citation
“…In line with such a neural underpinning, a series of studies suggested that reduced alpha power correlates with enhanced perceptual sensitivity (Ergenoglu, et al, 2004;Hanslmayr, et al, 2007;van Dijk, Schoffelen, Oostenveld, & Jensen, 2008;Mathewson, Gratton, Fabiani, Beck, & Ro, 2009;Busch, Dubois, & VanRullen, 2009;Obleser & Weisz, 2012). Yet, recent studies suggested a different picture whereby the alpha power does not modulate perceptual sensitivity or accuracy per se but rather reflects a bias in perceptual decision making (Limbach & Corballis, 2016;Iemi, Chaumon, Crouzet, & Busch, 2017;Samaha, Iemi, & Postle, 2017;Craddock, Poliakoff, El-deredy, Klepousniotou, & Lloyd, 2017;Iemi & Busch, 2018;Wöstmann, Waschke, & Obleser, 2018). While the precise role of alpha in a mechanistic cascade of sensory-decision processes remains debated, we here consider alpha oscillations from a new perspective, through the prism of idiosyncratic and temporary biases.…”
Section: A Mechanistic Role Of Alpha Powermentioning
confidence: 98%
“…Recent studies have suggested that pre-stimulus alpha activity may reflect the criterion used to commit a specific response and may hence reflect a perceptual or decisional bias (Limbach & Corballis, 2016;Iemi, Chaumon, Crouzet, & Busch, 2017;Craddock, Poliakoff, El-deredy, Klepousniotou, & Lloyd, 2017;Iemi & Busch, 2018;Rohe, Ehlis, & Noppeney, 2019). Along such a role in perceptual decision making, alpha activity was shown to correlate with subjective awareness (Benwell, et al, 2017;Lange, Oostenveld, & Fries, 2013;Gulbinaite, İlhan, & VanRullen, 2017) and decision confidence (Samaha, Iemi, & Postle, 2017;Wöstmann, Waschke, & Obleser, 2018). Still, it remains unclear whether pre-stimulus activity indeed reflects an individual's intrinsic bias, or reflects processes that facilitate veridical sensory encoding, as previous work did not unambiguously quantify the relation of spontaneous brain activity to idiosyncratic and temporary biases.…”
Section: Introductionmentioning
confidence: 99%
“…To test this relationship, a direct measure of cortical excitation is needed, ideally manifested in a well-defined neuronal process. Whereas previous studies proposed that alpha band activity reflects cortical excitability (Klimesch et al, 2007;Pfurtscheller, Stancák, & Neuper, 1996;Romei et al, 2008), its mechanistic underpinnings are still under debate (van Diepen, Foxe, & Mazaheri, 2019), and the modulatory role of alpha activity seems to be more pronounced for higher-level cognitive processes, such as perceptual confidence (Samaha, Iemi, & Postle, 2017), rather than for excitability on a more basic, neurophysiological level.…”
mentioning
confidence: 93%
“…At the same time, many other experiments imply the presence of dissociable neural circuits for perceptual decision making and confidence. Behaviorally, confidence judgments can be dissociated from the accuracy of the perceptual decision in both humans (Lau and Passingham, 2006;Rahnev et al, 2011bRahnev et al, , 2015Zylberberg et al, 2012Zylberberg et al, , 2016Vlassova et al, 2014;Spence et al, 2015;Koizumi et al, 2015;Song et al, 2015;Samaha et al, 2016Samaha et al, , 2017Boldt et al, 2017;Peters et al, 2017;Desender et al, 2018) and monkeys (Ferrigno et al, 2017), whereas other studies suggest that confidence judgments but not perceptual decisions are subject to late metacognitive noise (Mueller and Weidemann, 2008;Jang et al, 2012;De Martino et al, 2013;Maniscalco and Lau, 2016;Rahnev et al, 2016;van den Berg et al, 2017;Shekhar and Rahnev, 2018;Bang et al, 2019). Neurally, studies employing transcranial magnetic stimulation (TMS) delivered to the prefrontal cortex have been able to alter subjects' confidence ratings, while leaving their perceptual decisions unaffected (Rounis et al, 2010;Fleming et al, 2015;Rahnev et al, 2016;Shekhar and Rahnev, 2018).…”
Section: Introductionmentioning
confidence: 99%